Analysis of the Effect of Average Years of Schooling and Open Unemployment on the Gross Regional Domestic Product of Central Sulawesi Province, 2019-2023 - Triyudha Anugrah Farham; Santi Yunus; Mohamad Ichwan; Rita Yunus; Andi Herman Jaya (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2026)
The economy of Central Sulawesi Province shows fluctuating growth in Gross Regional Domestic Product (GRDP), with agriculture and mining as the primary drivers. Nevertheless, a number of obstacles remain, including sluggish economic growth in certain years, a relatively low Human Development Index as reflected in the Average Years of Schooling (RLS) indicator, and a continuing open unemployment problem. This situation highlights the need to understand how social factors relate to regional economic performance. This study seeks to examine the influence of Average Years of Schooling (RLS) and open unemployment on GRDP in Central Sulawesi Province. A quantitative approach employing panel data regression analysis is applied. Data spanning 2019 to 2023 are used to examine the relationship between RLS and open unemployment with respect to GRDP. The analysis reveals that RLS exerts a positive and significant influence on GRDP, with a 1 percent rise in RLS capable of raising GRDP by 3.162 percent. On the other hand, open unemployment has a negative and significant influence, whereby a 1 percent increase in open unemployment causes GRDP to fall by 0.222 percent. Overall, improvement of education quality through RLS is proven to drive regional economic growth, while high unemployment becomes an inhibiting factor for GRDP growth. Therefore, regional development policy needs to focus on improving access to and quality of education as well as creating job opportunities to reduce unemployment, so that the economic growth of Central Sulawesi can be more optimal.